Polyamic acid, polyamic acid solution, polyimide, polyimide film, laminate, electronic device and method for manufacturing a polyimide film

KR103031573B1Active Publication Date: 2026-10-13KANEKA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020237014949
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-22
Filing Date
2021-10-18
Publication Date
2026-10-13
Estimated Expiration
2041-10-18

Smart Images

  • Figure 112023048672343-PCT00010_ABST
    Figure 112023048672343-PCT00010_ABST
Patent Text Reader

Abstract

The polyamic acid has a tetravalent organic group represented by the following general formula (1) as a tetracarboxylic acid dianhydride residue, and also has one or more selected from the group consisting of p-phenylenediamine residues and (2-phenyl-4-aminophenyl)-4-aminobenzoate residues as diamine residues. The content of the tetravalent organic group represented by the following general formula (1) is 90 mol% or more and 100 mol% or less with respect to the total tetracarboxylic acid dianhydride residues. In the following general formula (1), R1 and R2 each independently represent a hydrogen atom, a halogen atom, an alkyl group with 1 to 12 carbon atoms, an alkenyl group with 2 to 12 carbon atoms, an alkoxy group with 1 to 12 carbon atoms, an aryl group with 6 to 14 carbon atoms, a hydroxyl group, a nitrile group, a nitro group, a carboxyl group, or an amide group.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to polyamide acid, a polyamide acid solution, polyimide, a polyimide film, a laminate, an electronic device, and a method for manufacturing a polyimide film. The present invention also relates to electronic device materials using polyimide, thin film transistor (TFT) substrates, flexible display substrates, color filters, printed materials, optical materials, image display devices (more specifically, liquid crystal display devices, organic EL, electronic paper, etc.), 3D displays, solar cells, touch panels, transparent conductive film substrates, and alternative materials for components currently using glass. Background Technology

[0002] With the rapid advancement of displays such as liquid crystal displays, organic EL, and electronic paper, as well as electronic devices such as solar cells and touch panels, devices are becoming thinner, lighter, and more flexible. In these devices, polyimide is being used as a substrate material instead of glass substrates.

[0003] In these devices, various electronic components, such as thin-film transistors or transparent electrodes, are formed on a substrate, and a high-temperature process is required for the formation of these electronic components. Polyimide possesses sufficient heat resistance to withstand high-temperature processes, and since its coefficient of linear expansion is close to that of glass substrates or electronic components, it is resistant to internal stress, making it suitable as a substrate material for flexible displays and the like.

[0004] Generally, aromatic polyimides are colored yellowish-brown due to the formation of intramolecular conjugations or charge transfer (CT) complexes. In top-emission organic ELs, light is emitted from the opposite side of the substrate, so transparency of the substrate is not required, and conventional aromatic polyimides have been used. However, in cases where light emitted from a display element is emitted through the substrate, such as in transparent displays, bottom-emission organic ELs, and liquid crystal displays, or when sensors or camera modules are placed on the back of the substrate to make smartphones and the like full-surface displays (notchless), high optical properties (more specifically, low colorability, etc.) are required for the substrate as well.

[0005] In addition, when a polyimide substrate is used in an image display device, if the retardation (Rth) in the thickness direction of the polyimide substrate is high, the display performance of the image display device tends to deteriorate.

[0006] Against this backdrop, there is a demand for a material that has a coefficient of linear expansion equivalent to that of conventional aromatic polyimides, while reducing discoloration and achieving low Rth.

[0007] Polyimide using monomers with a rigid structure is known as a plastic material that has a small coefficient of linear expansion (low thermal expansion) and high transparency (see, for example, Patent Document 1). In addition, Patent Document 2 describes that a polyimide film with excellent transparency and heat resistance is obtained by using a diamine having a fluorene structure. Prior art literature

[0008] Japanese Patent Publication No. 2007-046054 Japanese Patent Publication No. 2016-179969 The problem to be solved

[0009] However, with only the technology described in Patent Document 1 and Patent Document 2, it is difficult to obtain a polyimide that can reduce Rth while having low colorability and low thermal expansion.

[0010] The present invention has been made in consideration of the above circumstances and aims to provide a polyimide capable of reducing Rth, as well as having low colorability and low thermal expansion, and a polyamic acid as a precursor thereof. Furthermore, it aims to provide a product or component requiring low Rth, low colorability, and low thermal expansion, manufactured using said polyimide and polyamic acid. means of solving the problem

[0011] The polyamide acid related to the present invention has a tetravalent organic group represented by the following general formula (1) as a tetracarboxylic acid dianhydride residue, and also has one or more selected from the group consisting of p-phenylenediamine residue and (2-phenyl-4-aminophenyl)-4-aminobenzoate residue as a diamine residue. The content of the tetravalent organic group represented by the following general formula (1) is 90 mol% or more and 100 mol% or less with respect to the total tetracarboxylic acid dianhydride residue.

[0012]

[0013] Among the above general formula (1), R 1 and R 2 Each represents, independently, a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 14 carbon atoms, a hydroxyl group, a nitrile group, a nitro group, a carboxyl group, or an amide group.

[0014] In one embodiment of the polyamide acid related to the present invention, among the general formula (1), R 1 and R 2 All represent hydrogen atoms.

[0015] The polyamide acid related to one embodiment of the present invention further has one or more selected from the group consisting of a 4,4'-diaminobenzanilide residue, a 2,2'-bis(trifluoromethyl)benzidine residue, and a 9,9-bis(4-aminophenyl)fluorene residue as a diamine residue.

[0016] The polyamide acid solution related to the present invention contains the polyamide acid related to the present invention and an organic solvent.

[0017] The polyimide related to the present invention is an imid of a polyamide acid related to the present invention.

[0018] The polyimide related to the present invention preferably has a glass transition temperature of 350°C or higher.

[0019] The polyimide film related to the present invention comprises the polyimide related to the present invention.

[0020] The laminate related to the present invention has a support and a polyimide film related to the present invention.

[0021] An electronic device related to the present invention has a polyimide film related to the present invention and an electronic element disposed on said polyimide film.

[0022] A method for manufacturing a polyimide film related to the present invention forms a coating film containing said polyamide acid by applying a polyamide acid solution related to the present invention onto a support, and heats said coating film to imidize said polyamide acid.

[0023] In one embodiment of the method for manufacturing a polyimide film related to the present invention, the maximum temperature when heating the coating film is 380°C or higher and 500°C or lower.

[0024] In one embodiment of the method for manufacturing a polyimide film related to the present invention, the heating time at the maximum temperature is 5 minutes or more and 60 minutes or less.

[0025] In one embodiment of the method for manufacturing a polyimide film related to the present invention, the polyimide film obtained by heating the coating film is peeled off from the support.

[0026] In one embodiment of the method for manufacturing a polyimide film related to the present invention, the polyimide film is peeled off from the support by laser irradiation. Effects of the invention

[0027] The polyimide produced using the polyamide acid related to the present invention can reduce Rth and also exhibits excellent low colorability and low thermal expansion. Therefore, the polyimide produced using the polyamide acid related to the present invention is suitable as a material for electronic devices requiring low Rth, low colorability, and low thermal expansion. Specific details for implementing the invention

[0028] Suitable embodiments of the present invention will be described in detail below, but the present invention is not limited thereto.

[0029] First, the terms used in this specification will be explained. "Structural unit" refers to a repeating unit that constitutes a polymer. "Polyamic acid" is a polymer comprising a structural unit represented by the following general formula (2) (hereinafter referred to as "structural unit (2)").

[0030]

[0031] Among general formula (2), A 1 Silver represents a tetracarboxylic acid dianhydride residue (a tetravalent organic group derived from tetracarboxylic acid dianhydride), and A 2 represents a diamine residue (a divalent organic group derived from diamine).

[0032] The content of the structural unit (2) relative to the total structural unit constituting the polyamide acid is, for example, 50 mol% or more and 100 mol% or less, preferably 60 mol% or more and 100 mol% or less, more preferably 70 mol% or more and 100 mol% or less, even more preferably 80 mol% or more and 100 mol% or less, and even more preferably 90 mol% or more and 100 mol% or less, and may be 100 mol%.

[0033] "1% weight reduction temperature" is the measurement temperature at which the weight of the polyimide at a measurement temperature of 150°C is reduced by 1% relative to the weight of the reference weight (100% weight).

[0034] "The coefficient of linear expansion" is, if not specified at all, the coefficient of linear expansion when the temperature is lowered from 350°C to 100°C (coefficient of linear expansion when lowered).

[0035] The “alkyl group having 1 to 12 carbon atoms” is a straight chain or a branched chain and is unsubstituted. Examples of alkyl groups having 1 to 12 carbon atoms include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, s-butyl group, t-butyl group, n-pentyl group, isopentyl group, neopentyl group, n-hexyl group, n-heptyl group, n-octyl group, n-nonyl group, n-decyl group, n-undecyl group, and n-dodecyl group.

[0036] The “alkenyl group having 2 to 12 carbon atoms” is in a straight or branched chain form and is unsubstituted. Examples of alkenyl groups having 2 to 12 carbon atoms include vinyl group, 2-propenyl group, 3-butenyl group, 2-butenyl group, 4-pentenyl group, 3-pentenyl group, 2-hexenyl group, 3-hexenyl group, 5-hexenyl group, 2-heptenyl group, 3-heptenyl group, 4-heptenyl group, 3-octenyl group, 3-nonenyl group, 4-decenyl group, 3-undecenyl group, and 4-dodecenyl group.

[0037] The “alkoxy group with 1 to 12 carbon atoms” is in a straight or branched chain form and is unsubstituted. Examples of alkoxy groups with 1 to 12 carbon atoms include methoxy groups, ethoxy groups, n-propoxy groups, isopropoxy groups, n-butoxy groups, s-butoxy groups, t-butoxy groups, n-pentyloxy groups, isopentyloxy groups, neopentyloxy groups, n-hexyloxy groups, n-heptyloxy groups, n-octyloxy groups, n-nonyloxy groups, n-decyloxy groups, n-undecyloxy groups, and n-dodecyloxy groups.

[0038] "An aryl group having 6 to 14 carbon atoms" is unsubstituted. Examples of aryl groups having 6 to 14 carbon atoms include an unsubstituted aromatic monocyclic hydrocarbon group having 6 to 14 carbon atoms, an unsubstituted aromatic condensed bicyclic hydrocarbon group having 6 to 14 carbon atoms, and an unsubstituted aromatic condensed tricyclic hydrocarbon group having 6 to 14 carbon atoms. More specifically, examples of aryl groups having 6 to 14 carbon atoms include a phenyl group, a naphthyl group, anthryl group, and a phenanthryl group.

[0039] In the following cases, the term "system" may be added after the compound name to collectively refer to the compound and its derivatives. When the term "system" is added after the compound name to indicate the name of a polymer, it means that the repeating unit of the polymer is derived from the compound or its derivative. Additionally, tetracarboxylic acid dianhydrides may be referred to as "acid dianhydrides."

[0040] The polyamide acid related to the present embodiment has a tetravalent organic group represented by the following general formula (1) as a tetracarboxylic acid dianhydride residue, and also has one or more selected from the group consisting of p-phenylenediamine residues and (2-phenyl-4-aminophenyl)-4-aminobenzoate residues as diamine residues. It is preferable that the content of the tetravalent organic group represented by the following general formula (1) is 90 mol% or more and 100 mol% or less with respect to the total tetracarboxylic acid dianhydride residues constituting the polyamide acid related to the present embodiment.

[0041]

[0042] In general formula (1), R 1 and R 2 Each represents, independently, a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 14 carbon atoms, a hydroxyl group, a nitrile group, a nitro group, a carboxyl group, or an amide group. In order to facilitate imidation, R 1 and R 2 As for, independently, a hydrogen atom, a methyl group, or an ethyl group is preferred, and R 1 and R 2 a. It is particularly desirable that all represent hydrogen atoms. Accordingly, as the tetravalent organic group represented by general formula (1), a BPAF residue, which is a partial structure derived from 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride (hereinafter referred to as "BPAF"), is particularly desirable. That is, the polyamide acid related to this embodiment is A in general formula (2). 1 It is particularly desirable to have a BPAF residue as. Below, unless specifically mentioned, R in general formula (1) 1 and R 2 A, explain by assuming that all represent hydrogen atoms.

[0043] Because BPAF has a bulky fluorene structure, it can suppress the formation of charge transfer (CT) complexes. For this reason, BPAF is suitable as a monomer for polyimides with reduced coloration (low color). Furthermore, in polyimides using BPAF as a monomer, birefringence is less likely to occur because the fluorene rings derived from BPAF are twisted relative to the main chain. Therefore, BPAF is suitable as a monomer for polyimides capable of reducing Rth.

[0044] When synthesizing the polyamide acid related to the present embodiment, acid dianhydrides other than BPAF may be used as monomers within a range that does not impair the performance. Acid dianhydrides other than BPAF include, for example, pyromellitic acid dianhydride (hereinafter referred to as "PMDA"), 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (hereinafter referred to as "BPDA"), p-phenylenebis(trimellitate anhydride), 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 1,2,5,6-naphthalenetetracarboxylic acid dianhydride, 2,2',3,3'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, 4,4'-oxydiphthalic acid anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic acid anhydride, dicyclohexyl-3,3',4,4'-tetracarboxylic acid dianhydride, Examples include 1,2,4,5-cyclohexane tetracarboxylic acid dianhydride, 1,2,3,4-cyclobutane tetracarboxylic acid dianhydride, 2'-oxodispiro[bicyclo[2.2.1]heptane-2,1'-cyclopentane-3',2''-bicyclo[2.2.1]heptane]-5,6:5'',6''-tetracarboxylic acid dianhydride and derivatives thereof, and these may be used alone or in two or more types.

[0045] In order to obtain a polyimide capable of further reducing discoloration and Rth, it is preferable that the content of BPAF residues be 92 mol% or more with respect to the total tetracarboxylic acid dianhydride residues constituting the polyamide acid, more preferable that it be 95 mol% or more, even more preferable that it be 97 mol% or more, and particularly preferable that it be 100 mol% (having only BPAF residues as acid dianhydride residues).

[0046] When using an acid dianhydride other than BPAF as a monomer, from the perspective of improving heat resistance and mechanical strength, one or more selected from the group consisting of PMDA and BPDA are preferred as the acid dianhydride other than BPAF, and PMDA is more preferred. That is, when the polyamide acid related to the present embodiment has an acid dianhydride residue other than a BPAF residue as an acid dianhydride residue, one or more selected from the group consisting of PMDA residue and BPDA residue are preferred as the acid dianhydride residue other than a BPAF residue, and PMDA residue is more preferred.

[0047] In the case where the polyamide acid related to the present embodiment has one or more selected from the group consisting of PMDA residues and BPDA residues, in order to improve heat resistance and mechanical strength while reducing discoloration, the total content of PMDA residues and BPDA residues relative to the total acid dianhydride residues constituting the polyamide acid is preferably 1 mol% or more and 10 mol% or less, and more preferably 3 mol% or more and 7 mol% or less.

[0048] In the case where the polyamide acid related to the present embodiment has one or more selected from the group consisting of PMDA residues and BPDA residues, in order to improve heat resistance and mechanical strength while reducing discoloration and Rth, the total content of BPAF residues, PMDA residues, and BPDA residues relative to the total acid dianhydride residues constituting the polyamide acid is preferably 91 mol% or more, more preferably 93 mol% or more, even more preferably 95 mol% or more, even more preferably 97 mol% or more, and may be 100 mol%.

[0049] The polyamic acid related to the present embodiment has, as a diamine residue, one or more selected from the group consisting of a PDA residue which is a partial structure derived from p-phenylenediamine (hereinafter referred to as "PDA") and a PHBAAB residue which is a partial structure derived from (2-phenyl-4-aminophenyl)-4-aminobenzoate (hereinafter referred to as "PHBAAB"). That is, the polyamic acid related to the present embodiment is A in general formula (2). 2 It has one or more selected from the group consisting of PDA residues and PHBAAB residues. Since both PDA and PHBAAB have a rigid structure, they are suitable as low thermal expansion polyimide raw materials (monomers).

[0050] The PDA residue is a divalent organic group represented by the following chemical formula (3). Additionally, the PHBAAB residue is a divalent organic group represented by the following chemical formula (4).

[0051]

[0052] When synthesizing the polyamide acid related to the present embodiment, diamines other than PDA and PHBAAB may be used as monomers within a range that does not impair the performance. As diamines other than PDA and PHBAAB, for example, 4,4'-diaminobenzanilide (hereinafter referred to as "DABA"), 2,2'-bis(trifluoromethyl)benzidine (hereinafter referred to as "TFMB"), 9,9-bis(4-aminophenyl)fluorene (hereinafter referred to as "BAFL"), 4-aminophenyl-4-aminobenzoate, 1,4-diaminocyclohexane, m-phenylenediamine, 4,4'-oxydianiline, 3,4'-oxydianiline, 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether, N,N'-bis(4-aminophenyl)terephthalamide, 4,4'-diaminodiphenylsulfone, m-tolidine, o-tolidine, 4,4'-bis(4-aminophenoxy)biphenyl, Examples include 2-(4-aminophenyl)-6-aminobenzoxazole, 3,5-diaminobenzoic acid, 4,4'-diamino-3,3'-dihydroxybiphenyl, 4,4'-methylenebis(cyclohexanamine), 1,3-bis(3-aminopropyl)tetramethyldisiloxane, and derivatives thereof, and these may be used alone or in two or more types.

[0053] In order to reduce the coefficient of linear expansion, the total content of PDA residues and PHBAAB residues is preferably 0.1 mol% or more with respect to the total diamine residues constituting the polyamic acid, and may be 1.0 mol% or more, 10.0 mol% or more, 30.0 mol% or more, 50.0 mol% or more, 70.0 mol% or more, 90.0 mol% or more, 99.0 mol% or more, or 99.9 mol% or more, or 100.0 mol%. The polyamic acid related to the present embodiment may have only PDA residues, only PHBAAB residues, only PDA residues and PHBAAB residues, at least one of PDA residues and PHBAAB residues, and may also have diamine residues other than PDA residues and PHBAAB residues.

[0054] When using a diamine other than PDA and PHBAAB as a monomer, in order to further reduce coloration and Rth while making the coefficient of linear expansion smaller, it is preferable to use one or more selected from the group consisting of DABA, TFMB, and BAFL as the diamine other than PDA and PHBAAB. That is, when the polyamic acid related to the present embodiment has a diamine residue other than a PDA residue and a PHBAAB residue as a diamine residue, it is preferable to use one or more selected from the group consisting of a DABA residue, a TFMB residue, and a BAFL residue as the diamine residue other than the PDA residue and the PHBAAB residue.

[0055] In order to further reduce the coefficient of linear expansion, it is preferable that the polyamide acid related to the present embodiment has a DABA residue as a diamine residue. When the polyamide acid related to the present embodiment has a DABA residue, in order to further reduce the coefficient of linear expansion, it is preferable that the content of the DABA residue be 0.1 mol% or more with respect to the total diamine residue constituting the polyamide acid, and may be 1.0 mol% or more, 10.0 mol% or more, 30.0 mol% or more, 50.0 mol% or more, 70.0 mol% or more, 90.0 mol% or more, or 99.0 mol% or more, or may be 99.0 mol% or more and 99.9 mol% or less.

[0056] In order to further reduce discoloration, it is preferable that the polyamide acid related to the present embodiment has a TFMB residue as a diamine residue. When the polyamide acid related to the present embodiment has a TFMB residue, in order to further reduce discoloration, it is preferable that the content of the TFMB residue be 0.1 mol% or more with respect to the total diamine residue constituting the polyamide acid, and may be 1.0 mol% or more, 10.0 mol% or more, 30.0 mol% or more, 50.0 mol% or more, 70.0 mol% or more, 90.0 mol% or more, or 99.0 mol% or more, or may be 99.0 mol% or more and 99.9 mol% or less.

[0057] In order to further reduce Rth, it is preferable that the polyamide acid related to the present embodiment has a BAFL residue as a diamine residue. When the polyamide acid related to the present embodiment has a BAFL residue, in order to further reduce Rth, it is preferable that the content of the BAFL residue be 0.1 mol% or more with respect to the total diamine residue constituting the polyamide acid, and may be 1.0 mol% or more, 10.0 mol% or more, or 30.0 mol% or more, or may be 30.0 mol% or more and 50.0 mol% or less.

[0058] In the case where the polyamide acid related to the present embodiment has one or more selected from the group consisting of DABA residues, TFMB residues, and BAFL residues, in order to further reduce coloration and Rth while making the coefficient of linear expansion smaller, the total content of PDA residues, PHBAAB residues, DABA residues, TFMB residues, and BAFL residues relative to the total diamine residues constituting the polyamide acid is preferably 90.0 mol% or more, more preferably 93.0 mol% or more, even more preferably 95.0 mol% or more, even more preferably 97.0 mol% or more, and may be 100.0 mol%.

[0059] In order to obtain a polyimide capable of further reducing the coefficient of linear expansion while further reducing discoloration and Rth, the polyamic acid related to the present embodiment preferably satisfies Condition 1 below, more preferably satisfies Conditions 1 and 2 below, and more preferably satisfies Conditions 1, 2, and 3 below. To particularly reduce the coefficient of linear expansion, it is preferable to satisfy Conditions 1 and 4 below. To particularly reduce discoloration, it is preferable to satisfy Conditions 1 and 5 below. To particularly reduce Rth, it is preferable to satisfy Conditions 1 and 6 below.

[0060] Condition 1: The polyamide acid has only a BPAF residue as the acid dianhydride residue.

[0061] Condition 2: The polyamide acid further has one or more diamine residues selected from the group consisting of DABA residues, TFMB residues, and BAFL residues.

[0062] Condition 3: The total content of PDA residue, PHBAAB residue, DABA residue, TFMB residue and BAFL residue with respect to the total diamine residues constituting the polyamide acid is 100.0 mol%.

[0063] Condition 4: The polyamide acid has only PDA residues and DABA residues as diamine residues.

[0064] Condition 5: The polyamide acid has only PDA residues and TFMB residues as diamine residues, or only PHBAAB residues and TFMB residues.

[0065] Condition 6: The polyamide acid has only PDA residues and BAFL residues as diamine residues, or has only PDA residues and PHBAAB residues.

[0066] In order to suppress the decrease in transparency caused by the retention of unreacted monomers during polyimide formation, it is preferable that the total amount of tetracarboxylic acid dianhydride residues divided by the total amount of diamine residues has a material amount ratio (molar ratio) of 0.900 or more and less than 1.100, and more preferable that it has a material amount ratio of 0.950 or more and 1.080 or less. By adjusting the material amount ratio to within the above range, a polyimide with excellent transparency is obtained.

[0067] The polyamic acid of the present invention can be synthesized by known general methods, for example, by reacting a diamine with a tetracarboxylic acid dianhydride in an organic solvent. The monomer components used in the synthesis of the polyamic acid may include components other than the diamine and the tetracarboxylic acid dianhydride. For example, a monofunctional amine or a monofunctional acid anhydride may be used for purposes such as adjusting the molecular weight. An example of a specific synthesis method for the polyamic acid is described. First, a diamine solution is prepared by dissolving the diamine in an organic solvent or dispersing it in a slurry state under an inert gas atmosphere such as argon or nitrogen. Then, the tetracarboxylic acid dianhydride is dissolved in an organic solvent or dispersed in a slurry state, or added to the diamine solution in a solid state.

[0068] When synthesizing polyamide acid using a diamine and a tetracarboxylic acid dianhydride, a desired polyamide acid (a polymer of diamine and tetracarboxylic acid dianhydride) can be obtained by adjusting the amount of diamine (the amount of each diamine when multiple types of diamine are used) and the amount of tetracarboxylic acid dianhydride (the amount of each tetracarboxylic acid dianhydride when multiple types of tetracarboxylic acid dianhydride are used). The mole fraction of each residue in the polyamide acid matches, for example, the mole fraction of each monomer (diamine and tetracarboxylic acid dianhydride) used in the synthesis of the polyamide acid. In addition, by blending two types of polyamide acid, a polyamide acid containing multiple types of tetracarboxylic acid dianhydride residues and multiple types of diamine residues can also be obtained. The temperature conditions for the reaction between a diamine and a tetracarboxylic acid dianhydride, i.e., the synthesis reaction of polyamic acid, are not particularly limited, but are, for example, in the range of 20°C to 150°C. The reaction time for the synthesis reaction of polyamic acid is, for example, in the range of 10 minutes to 30 hours.

[0069] The organic solvent used for the synthesis of polyamic acid is preferably a solvent capable of dissolving the tetracarboxylic acid dianhydride and diamine used, and more preferably a solvent capable of dissolving the polyamic acid produced. Examples of organic solvents used for the synthesis of polyamic acid include urea-based solvents such as tetramethylurea and N,N-dimethylethylurea; sulfoxide-based solvents such as dimethyl sulfoxide; sulfone-based solvents such as diphenylsulfone and tetramethylsulfone; amide-based solvents such as N,N-dimethylacetamide (DMAC), N,N-dimethylformamide (DMF), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), and hexamethylphosphate triamide; ester-based solvents such as γ-butyrolactone; alkyl halide-based solvents such as chloroform and methylene chloride; aromatic hydrocarbon-based solvents such as benzene and toluene; and phenol-based solvents such as phenol and cresol. Examples include ketone-based solvents such as cyclopentanone; and ether-based solvents such as tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, dimethyl ether, diethyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, and p-cresol methyl ether. Typically, these solvents are used individually, but if necessary, two or more may be used in an appropriate combination. To increase the solubility and reactivity of polyamic acid, one or more solvents selected from the group consisting of amide-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents are preferred as organic solvents used in the synthesis reaction of polyamic acid, and amide-based solvents (more specifically, DMF, DMAC, NMP, etc.) are more preferred. Furthermore, it is preferable to carry out the synthesis reaction of polyamic acid under an inert gas atmosphere such as argon or nitrogen.

[0070] The weight average molecular weight of the polyamide acid related to the present embodiment varies depending on the application, but it is preferably in the range of 10,000 to 1,000,000, more preferably in the range of 20,000 to 500,000, and even more preferably in the range of 30,000 to 200,000. If the weight average molecular weight is 10,000 or more, it becomes easy to form the polyamide acid, or the polyimide obtained using the polyamide acid, into a coating film or a polyimide film. On the other hand, if the weight average molecular weight is 1,000,000 or less, it exhibits sufficient solubility in a solvent, so a coating film or a polyimide film with a smooth surface and uniform thickness can be obtained by using the polyamide acid solution described below. The weight average molecular weight used herein refers to the polyethylene oxide equivalent value measured using gel permeation chromatography (GPC).

[0071] The polyamide acid solution related to the present embodiment comprises the polyamide acid related to the present embodiment described above and an organic solvent. Here, the organic solvent included in the polyamide acid solution may be an organic solvent exemplified as an organic solvent usable in the synthesis reaction of the polyamide acid, and one or more solvents selected from the group consisting of amide-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents are preferred, and an amide-based solvent (more specifically, DMF, DMAC, NMP, etc.) is more preferred. When polyamide acid is obtained by the method described above, the reaction solution (solution after reaction) itself may be the polyamide acid solution related to the present embodiment. In addition, the solid polyamide acid obtained by removing the solvent from the reaction solution may be dissolved in an organic solvent to prepare the polyamide acid solution related to the present embodiment. In addition, the content of polyamide acid in the polyamide acid solution related to the present embodiment is not particularly limited, but, for example, is 1% by weight or more and 80% by weight or less with respect to the total amount of the polyamide acid solution.

[0072] The polyimide related to the present embodiment is an imidized form of the polyamic acid related to the present embodiment described above. The polyimide related to the present embodiment can be obtained by known methods, and its manufacturing method is not particularly limited. Below, an example of a method for obtaining the polyimide related to the present embodiment by imidizing the above polyamic acid is described. Imidization is performed by dehydrating and ring-closing the polyamic acid. This dehydration and ring-closing can be performed by an azeotropic method using an azeotropic solvent, a thermal method, or a chemical method. Furthermore, the imidization from the polyamic acid to the polyimide can take any ratio of 1% or more and 100% or less. That is, a polyamic acid in which a portion has been imidized may be synthesized. In particular, when imidization occurs through heating and raising the temperature, the ring-closing reaction from polyamic acid to polyimide and the hydrolysis of polyamic acid proceed simultaneously, and since there is a possibility that the molecular weight of the polyimide will be lower than that of the polyamic acid, it is desirable from the perspective of improving mechanical properties to pre-imidize a portion of the polyamic acid in the polyamic acid solution before forming the polyimide film described below. In this specification, polyamic acid that has been partially imidized may also be referred to as "polyamic acid."

[0073] The dehydration and ring closure of polyamide acid can be performed by heating the polyamide acid. The method of heating the polyamide acid is not particularly limited, but for example, a polyamide acid solution related to the present embodiment described above may be applied to a support such as a glass substrate, a metal plate, or a PET film (polyethylene terephthalate film), and then heat treatment of the polyamide acid may be performed within a temperature range of 40°C to 500°C. According to this method, a laminate related to the present embodiment is obtained having a support and a polyimide film disposed on the support (specifically, a polyimide film containing an imide of the polyamide acid related to the present embodiment). Alternatively, the dehydration and ring closure of the polyamide acid may be performed by directly placing the polyamide acid solution into a container that has undergone a release treatment, such as coating with a fluorine-based resin, and heating and drying the polyamide acid solution under reduced pressure. Polyimide can be obtained by the dehydration and ring closure of the polyamide acid by these methods. In addition, the heating time for each of the above treatments varies depending on the amount of polyamide acid solution to be dehydrated and the heating temperature, but generally, it is preferable to have the treatment temperature in the range of 1 minute or more and 300 minutes or less after reaching the maximum temperature, and more preferable to have it in the range of 5 minutes or more and 60 minutes or less. In addition, to shorten the heating time or to develop characteristics, an imidizing agent and / or a dehydration catalyst may be added to the polyamide acid solution, and the polyamide acid solution to which the imidizing agent and / or dehydration catalyst have been added may be heated by the above method to induce imidization.

[0074] As the imidizing agent mentioned above, tertiary amines may be used, although they are not particularly limited. As the tertiary amine, a heterocyclic tertiary amine is preferred. Preferred specific examples of heterocyclic tertiary amines include pyridine, picoline, quinoline, isoquinoline, 1,2-dimethylimidazole, etc. As the dehydration catalyst mentioned above, preferred specific examples include acetic anhydride, propionic anhydride, n-butyric anhydride, benzoic anhydride, trifluoroacetic anhydride, etc.

[0075] As for the amount of imidizing agent added, it is preferable to have an amount of 0.5 molar equivalents or more and 5.0 molar equivalents or less relative to the amide group of the polyamic acid, more preferable to have an amount of 0.7 molar equivalents or more and 2.5 molar equivalents or less relative to the amide group of the polyamic acid, and even more preferable to have an amount of 0.8 molar equivalents or more and 2.0 molar equivalents or less relative to the amide group of the polyamic acid. In addition, as for the amount of dehydration catalyst added, it is preferable to have an amount of 0.5 molar equivalents or more and 10.0 molar equivalents or less relative to the amide group of the polyamic acid, more preferable to have an amount of 0.7 molar equivalents or more and 5.0 molar equivalents or less relative to the amide group of the polyamic acid, and even more preferable to have an amount of 0.8 molar equivalents or more and 3.0 molar equivalents or less relative to the amide group of the polyamic acid. In addition, in this specification, "amide group of the polyamic acid" refers to an amide group produced by the polymerization reaction of a diamine and a tetracarboxylic acid dianhydride. When adding an imidizing agent and / or a dehydration catalyst to a polyamide acid solution, they may be added directly without dissolving in an organic solvent, or they may be added after being dissolved in an organic solvent. In the method of adding directly without dissolving in an organic solvent, the reaction proceeds rapidly before the imidizing agent and / or the dehydration catalyst diffuse, which may result in the formation of a gel. Therefore, it is preferable to add the solution obtained by dissolving the imidizing agent and / or the dehydration catalyst in an organic solvent to the polyamide acid solution.

[0076] The polyimide film related to the present embodiment (specifically, a polyimide film comprising an imide of a polyamide acid related to the present embodiment) is colorless and transparent, has a low yellowness, and has a glass transition temperature (heat resistance) capable of withstanding the TFT manufacturing process, making it suitable as a transparent substrate material for a flexible display. The content of polyimide (specifically, an imide of a polyamide acid related to the present embodiment) in the polyimide film related to the present embodiment is, for example, 70 weight% or more with respect to the total amount of the polyimide film, preferably 80 weight% or more, more preferably 90 weight% or more, and may be 100 weight%. As for components other than polyimide in the polyimide film, for example, the additive described below (more specifically, nanosilica particles, etc.) may be cited.

[0077] The electronic device related to the present embodiment has a polyimide film related to the present embodiment and an electronic element disposed directly or indirectly on the polyimide film. When manufacturing the electronic device related to the present embodiment for a flexible display, first, an inorganic substrate such as glass is used as a support, and a polyimide film is formed thereon. Then, an electronic device is formed on the support by disposing of (forming) an electronic element such as a TFT on the polyimide film. The process of forming the TFT is generally carried out in a wide temperature range of 150°C or higher and 650°C or lower; however, to actually achieve the desired performance, an oxide semiconductor layer or an a-Si layer is formed at 300°C or higher, and in some cases, a-Si, etc., may also be crystallized using a laser, etc.

[0078] At this time, if the thermal decomposition temperature of the polyimide film is low, outgas may be generated during the formation of the electronic device and adhere to the inside of the oven as a sublimate, causing contamination inside the oven or potentially causing the inorganic film (such as the barrier film described later) or the electronic device formed on the polyimide film to peel off. Therefore, it is desirable that the 1% weight loss temperature of the polyimide be 500°C or higher. To explain in more detail, before forming the TFT, an inorganic film such as a silicon oxide film (SiOx film) or a silicon nitride film (SiNx film) is formed as a barrier film on the polyimide film. If the heat resistance of the polyimide is low, the polyimide and the inorganic film may peel off due to volatile components such as decomposition gases of the polyimide during the high-temperature process after the inorganic film is laminated. For this reason, in addition to the 1% weight loss temperature of the polyimide being 500°C or higher, it is desirable that the weight loss rate when the polyimide is isothermally maintained at a temperature within the range of 400°C or higher and 450°C or lower is less than 1%.

[0079] In addition, if the glass transition temperature (Tg) of the polyimide is significantly lower than the process temperature, there is a possibility that positional misalignment may occur during the formation of electronic devices; therefore, it is preferable that the Tg of the polyimide be 300°C or higher, more preferable that it be 350°C or higher, and even more preferable that it be 400°C or higher. The upper limit of the polyimide's Tg is preferably as high as possible, but for example, it is 450°C. The Tg of the polyimide can be adjusted, for example, by changing the content of residues having a rigid structure (more specifically, PDA residues, PHBAAB residues, etc.). Furthermore, since the coefficient of linear expansion of the glass substrate is generally smaller compared to that of the resin, internal stress occurs between the glass substrate and the polyimide film. If the internal stress of the laminate of the glass substrate used as a support and the polyimide film is high, the laminate containing the polyimide film expands during the high-temperature TFT formation process and then shrinks when cooled to room temperature, causing problems such as warping or breakage of the glass substrate and delamination of the polyimide film from the glass substrate. Therefore, it is desirable that the internal stress generated in the laminate of the polyimide film and the glass substrate be 50 MPa or less.

[0080] In order to suppress the occurrence of the above internal stress, it is preferable that the linear expansion coefficient of the polyimide film be 100 ppm / K or less, more preferable that it be 90 ppm / K or less, and even more preferable that it be 80 ppm / K or less. The linear expansion coefficient of the polyimide film may be -10 ppm / K or more and 80 ppm / K or less, 0 ppm / K or more and 80 ppm / K or less, 10 ppm / K or more and 80 ppm / K or less, 20 ppm / K or more and 80 ppm / K or less, 30 ppm / K or more and 80 ppm / K or less, 40 ppm / K or more and 80 ppm / K or less, or 50 ppm / K or more and 80 ppm / K or less.

[0081] In order to suppress the degradation of display performance when applied to an image display device, the thickness direction retardation (Rth) of the polyimide film for light of a wavelength of 550 nm is preferably 200 nm or less, more preferably 100 nm or less, even more preferably 90 nm or less, even more preferably 80 nm or less, and particularly preferably 70 nm or less, as converted to a value of a polyimide film with a thickness of 10 μm.

[0082] The transparency of a polyimide film can be evaluated by total light transmittance (TT) according to JIS K7361-1:1997, the transmittance of light at a wavelength of 450 nm (hereinafter referred to simply as "light transmittance"), and haze according to JIS K7136-2000. When a polyimide film is used for applications requiring high transparency, the total light transmittance of the polyimide film is preferably 75% or higher, and more preferably 80% or higher. Furthermore, when a polyimide film is used for applications requiring high transparency, the light transmittance of the polyimide film is preferably 75% or higher, and more preferably 78% or higher. Additionally, when a polyimide film is used for applications requiring high transparency, the haze of the polyimide film is preferably 1.5% or lower, more preferably 1.2% or lower, and even more preferably less than 1.0%. For applications requiring high transparency, polyimide films are required to have high transmittance across the entire wavelength range; however, polyimide films tend to easily absorb light on the short-wavelength side, and the film itself often becomes colored yellow. To use polyimide films for applications requiring high transparency, it is preferable that the yellowness (YI) of the polyimide film be 25 or less, more preferable that it be 20 or less, even more preferable that it be 14 or less, and particularly preferable that it be 12 or less. YI can be measured according to JIS K7373-2006. Polyimide films with such imparted transparency are suitable for transparent substrates, such as glass replacement applications, or for substrates on which sensors or camera modules are provided on the back surface.

[0083] In addition, there are two types of light extraction methods for flexible displays: a top emission method that extracts light from the surface side of the TFT and a bottom emission method that extracts light from the back side of the TFT. The top emission method is characterized by the fact that light is not blocked by the TFT, making it easy to increase the aperture ratio and thus obtain high-precision image quality, while the bottom emission method is characterized by the fact that alignment of the TFT and pixel electrodes is easy and manufacturing is easy. Since it is possible to improve the aperture ratio even in the bottom emission method when the TFT is transparent, the bottom emission method, which is easy to manufacture, tends to be adopted for large displays. The polyimide film related to the present embodiment has a low YI and excellent heat resistance, so it can be applied to either of the above light extraction methods.

[0084] In the manufacturing process of electronic devices, electronic components such as thin-film transistors or transparent electrodes are formed on a substrate. The process of forming electronic components on a polyimide substrate is divided into a batch process and a roll-to-roll process. In the roll-to-roll process, electronic components are sequentially formed on the polyimide substrate (polyimide film) while conveying a long polyimide substrate. In the batch process, a laminate is formed by, for example, forming a polyimide substrate (polyimide film) on a glass support, and after forming electronic components on the polyimide film of the laminate, the support is peeled off from the polyimide film. The polyimide related to the present embodiment is applicable to either process. The batch process has an advantage in terms of cost because it can utilize existing equipment for glass supports.

[0085] The polyimide related to the present embodiment can be suitably used as a material for display substrates, such as TFT substrates or touch panel substrates. When using the polyimide for the above applications, as described above, a method is often adopted in which an electronic device (specifically, an electronic device in which an electronic element is formed on a polyimide film) is formed on a support, and then the polyimide film is peeled off from the support. In addition, alkali-free glass is suitably used as the material for the support. Below, an example of a method for manufacturing a polyimide film related to the present embodiment and an example of a method for manufacturing a laminate (a laminate of a polyimide film and a support) related to the present embodiment will be described in detail.

[0086] First, a polyamide acid solution related to the present embodiment is applied onto a support, and a coating film-containing laminate comprising a coating film containing polyamide acid and a support is formed. Subsequently, the coating film-containing laminate is heated, for example, under conditions of a temperature of 40°C or higher and 200°C or lower. The heating time at this time is, for example, 3 minutes or more and 120 minutes or less. In addition, a multi-stage heating process may be provided, such as heating the coating film-containing laminate at 50°C for 30 minutes and then heating at 100°C for 30 minutes. Subsequently, in order to proceed with the imidization of the polyamide acid in the coating film, the coating film-containing laminate (polyamide acid film-containing laminate) is heated, for example, under conditions of a maximum temperature of 250°C or higher and 500°C or lower. The heating time at this time (heating time at the maximum temperature) is, for example, 1 minute or more and 300 minutes or less, and preferably 5 minutes or more and 60 minutes or less. At this time, it is preferable to gradually increase the temperature from a low temperature to a maximum temperature. The heating rate is preferably 2°C / min or higher and 10°C / min or lower, and more preferably 4°C / min or higher and 10°C / min or lower. Additionally, the maximum temperature is preferably in the range of 380°C or higher and 500°C or lower. If the maximum temperature is 380°C or higher, sufficient imidation proceeds, and if the maximum temperature is 500°C or lower, thermal degradation of the polyimide can be suppressed. Furthermore, the temperature may be maintained at any temperature for any time until the maximum temperature is reached. The imidation reaction may be carried out under air, under reduced pressure, or in an inert gas such as nitrogen, but to achieve higher transparency, it is preferable to carry out the reaction under reduced pressure or in an inert gas such as nitrogen. Additionally, known devices such as a hot air oven, infrared oven, vacuum oven, inert oven, or hot plate may be used as the heating device.Through these processes, the polyamide acid in the coating film is imidized, thereby obtaining a laminate of a support and a polyimide film (a polyimide film containing an imid of the polyamide acid related to the present embodiment). Additionally, by peeling off the polyimide film formed on the support from the support, for example, by the method described below, a polyimide film related to the present embodiment (a polyimide film containing an imid of the polyamide acid related to the present embodiment) can be obtained. An electronic device may be provided on the polyimide film peeled off from the support. Furthermore, to shorten the heating time or to improve the expression of characteristics, an imidizing agent or a dehydration catalyst may be added to the polyamide acid solution, and the solution may be heated by the above method to induce imidization.

[0087] A known method may be used to peel off the polyimide film from the laminate of the obtained support and the polyimide film. For example, it may be peeled off by hand or by using a mechanical device such as a drive roller or a robot. Furthermore, a method may be adopted in which a peeling layer is provided between the support and the polyimide film, or a method may be adopted in which a silicon oxide film is formed on a substrate having a plurality of grooves, a polyimide film is formed using the silicon oxide film as a base layer, and a silicon oxide etching solution is infiltrated between the substrate and the silicon oxide film to peel off the polyimide film. Additionally, a method may be adopted in which the polyimide film is peeled off from the support by irradiation with laser light.

[0088] In addition, in a batch-type device manufacturing process in which a polyamide acid solution is applied onto a support such as a glass substrate, heated to induce imidation, and then an electronic device is formed and the polyimide film is peeled off, it is desirable that there be excellent adhesion between the support and the polyimide film. The adhesion referred to here means adhesion strength. In a manufacturing process in which an electronic device is formed on a polyimide film on a support and then the polyimide film on which the electronic device is formed is peeled off from the support, if the adhesion between the polyimide film and the support is excellent, the electronic device can be formed or mounted more accurately. In a manufacturing process in which an electronic device is placed on a support through a polyimide film, from the perspective of improving productivity, the higher the peel strength between the support and the polyimide film, the better. Specifically, the above peel strength is preferably 0.05 N / cm or higher, and more preferably 0.1 N / cm or higher.

[0089] In the manufacturing process described above, when peeling off the polyimide film from a laminate of a support and a polyimide film, the polyimide film is often peeled off from the support by laser irradiation. In this case, since it is necessary to absorb laser light into the polyimide film, the cutoff wavelength of the polyimide film is required to be longer than the wavelength of the laser light used for peeling. Since a XeCl excimer laser with a wavelength of 308 nm is often used for laser peeling, it is preferable that the cutoff wavelength of the polyimide film be 312 nm or longer, and more preferable that it be 330 nm or longer. On the other hand, since the polyimide film tends to be colored yellow if the cutoff wavelength is long, it is preferable that the cutoff wavelength of the polyimide film be 390 nm or shorter. In terms of achieving compatibility between transparency (low yellowness) and processability for laser peeling, the cutoff wavelength of the polyimide film is preferably 320 nm or more and 390 nm or less, and more preferably 330 nm or more and 380 nm or less. In addition, the cutoff wavelength in this specification refers to a wavelength at which the transmittance measured by an ultraviolet-visible spectrophotometer becomes 0.1% or less.

[0090] The polyamic acid and polyimide related to the present embodiment may be used as is in a coating or molding process for producing products or components, but may also be used as materials for performing additional treatments such as coating on a molded article formed into a film. For use in a coating or molding process, the polyamic acid or polyimide may be dissolved or dispersed in an organic solvent as needed, and a photocurable component, a thermosetting component, a non-polymerizable binder resin, and other components may be combined as needed to prepare a polyamic acid composition or a polyimide resin composition.

[0091] In order to impart processing characteristics or various functionalities to the polyamic acid and polyimide related to the present embodiment, various organic or inorganic low-molecular-weight compounds or high-molecular-weight compounds may be added to the polyamic acid solution as additives. Examples of additives may include dyes, surfactants, leveling agents, plasticizers, silicones, microparticles, sensitizers, etc. Microparticles may include organic microparticles such as polystyrene and polytetrafluoroethylene, or inorganic microparticles such as colloidal silica, carbon, and layered silicates, and they may have a porous structure or a hollow structure. Furthermore, the function and form of the microparticles are not particularly limited and may be, for example, pigments, fillers, or fibrous particles.

[0092] In order to improve heat resistance while maintaining the transparency of the polyimide film, nanosilica particles may be used as the additive to composite the polyamide acid and nanosilica particles. From the perspective of maintaining the transparency of the polyimide film, the average primary particle size of the nanosilica particles is preferably 200 nm or less, more preferably 100 nm or less, even more preferably 50 nm or less, and may be 30 nm or less. Meanwhile, from the perspective of ensuring dispersibility with respect to the polyamide acid, the average primary particle size of the nanosilica particles is preferably 5 nm or more, and more preferably 10 nm or more. As a method for compositing the polyamide acid and nanosilica particles, known methods may be used, for example, a method using an organosilica sol in which nanosilica particles are dispersed in an organic solvent. As a method for compounding polyamide acid and nanosilica particles using organosilica sol, polyamide acid may be synthesized and then the synthesized polyamide acid may be mixed with organosilica sol, but in order to disperse nanosilica particles more highly in the polyamide acid, it is preferable to synthesize the polyamide acid in the organosilica sol.

[0093] In addition, to enhance interaction with polyamide acid, nanosilica particles may be surface-treated with a surface treatment agent. Known agents, such as silane coupling agents, may be used as surface treatment agents. As silane coupling agents, alkoxysilane compounds having functional groups such as amino groups or glycidyl groups are widely known and can be appropriately selected. To further enhance interaction with polyamide acid, an amino group-containing alkoxysilane is preferred as the silane coupling agent. Examples of amino group-containing alkoxysilanes include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-phenylaminopropyltrimethoxysilane, 2-aminophenyltrimethoxysilane, and 3-aminophenyltrimethoxysilane; however, from the perspective of raw material stability, it is preferable to use 3-aminopropyltriethoxysilane. As a surface treatment method for nanosilica particles, a method of stirring a mixture in which a silane coupling agent is added to a dispersion (organosilica sol) under an atmosphere temperature of 20°C to 80°C may be used. The stirring time at this time is, for example, 1 hour to 10 hours. At this time, a catalyst that promotes the reaction may be added.

[0094] A polyamide acid composition containing nanosilica particles, formed by combining polyamide acid and nanosilica particles, preferably contains nanosilica particles in a range of 1 part by weight or more and 30 parts by weight or less per 100 parts by weight of polyamide acid, and more preferably contains nanosilica particles in a range of 1 part by weight or more and 20 parts by weight or less. If the content of nanosilica particles is 1 part by weight or more, the heat resistance of the polyimide containing nanosilica particles can be improved to sufficiently reduce internal stress, and if the content of nanosilica particles is 30 parts by weight or less, adverse effects on the mechanical properties and transparency of the polyimide containing nanosilica particles can be suppressed.

[0095] In the polyamide acid related to the present embodiment, imidazoles may be added as additives for imparting the aforementioned functionality. In this specification, imidazoles refer to compounds having a 1,3-diazo ring (1,3-diazo ring structure). The imidazoles added to the polyamide acid related to the present embodiment are not particularly limited, but examples include 1H-imidazole, 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, etc. Among these, 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-phenylimidazole are preferred, and 1,2-dimethylimidazole and 1-benzyl-2-methylimidazole are more preferred.

[0096] The content of imidazoles is preferably 0.005 moles or more and 0.1 moles or less per 1 mole of amide group of polyamide acid, more preferably 0.01 moles or more and 0.08 moles or less, and even more preferably 0.015 moles or more and 0.050 moles or less. By including 0.005 moles or more of imidazoles, the film strength and transparency of the polyimide can be improved, and by keeping the content of imidazoles 0.1 moles or less, the storage stability of the polyamide acid can be maintained while improving Tg and heat resistance.

[0097] The method of mixing polyamic acid and imidazoles is not particularly limited. From the perspective of ease of controlling the molecular weight of polyamic acid, it is preferable to add imidazoles to the polyamic acid after polymerization. At this time, the imidazoles may be added directly to the polyamic acid, or the imidazoles may be dissolved in a solvent beforehand and this solution added to the polyamic acid; the method of addition is not particularly limited. The imidazoles may be added to a solution containing the polyamic acid after polymerization (solution after reaction) to prepare a polyamic acid solution (a solution containing polyamic acid and imidazoles) related to the present embodiment.

[0098] In addition, the polyamide acid solution related to the present embodiment may contain a silane coupling agent to exhibit appropriate adhesion to the support. The silane coupling agent may be added to the monomer solution before the polymerization reaction, to the solution during the polymerization reaction, or to the polyamide acid solution after the polymerization reaction. The type of silane coupling agent may be any known type without particular limitation, but a compound containing an amino group is particularly preferred from the perspective of reactivity with the polyamide acid.

[0099] The mixing ratio of the silane coupling agent to 100 parts by weight of polyamide acid is preferably 0.01 parts by weight or more and 0.50 parts by weight or less, more preferably 0.01 parts by weight or more and 0.10 parts by weight or less, and even more preferably 0.01 parts by weight or more and 0.05 parts by weight or less. By making the mixing ratio of the silane coupling agent 0.01 parts by weight or more, the peeling inhibition effect on the support is sufficiently exhibited, and by making the mixing ratio of the silane coupling agent 0.50 parts by weight or less, the decrease in the molecular weight of the polyamide acid is inhibited, so the embrittlement of the polyimide film can be inhibited.

[0100] Various inorganic thin films, such as metal oxide thin films or transparent electrodes, may be formed on the surface of the polyimide film related to the present embodiment. The method for forming these inorganic thin films is not particularly limited, and examples include CVD, sputtering, vacuum deposition, PVD methods such as ion plating, etc.

[0101] The polyimide film related to the present embodiment is preferably used in fields and products where these properties are effective, as it has low internal stress when forming a laminate with a glass substrate in addition to heat resistance, low thermal expansion, and transparency. For example, the polyimide film related to the present embodiment is preferably used in image display devices such as liquid crystal displays, organic ELs, and electronic paper, printed materials, color filters, flexible displays, optical films, 3D displays, touch panels, transparent conductive film substrates, solar cells, etc. Furthermore, it is more preferable to use it as a substitute material for parts where glass is currently used. For these applications, the thickness of the polyimide film is preferably, for example, 1 μm or more and 200 μm or less, and 5 μm or more and 100 μm or less. The thickness of the polyimide film can be measured using a laser hologage.

[0102] In addition, the polyamide acid solution related to the present embodiment can be suitably used in a batch-type device manufacturing process in which the polyamide acid solution is applied onto a support, heated to induce imidation, and after forming an electronic element, the like, the polyimide film is peeled off. Accordingly, the present embodiment also includes a method for manufacturing an electronic device comprising the steps of applying a polyamide acid solution onto a support, heating to induce imidation, and forming an electronic element, the like, on a polyimide film formed on the support. Furthermore, such a method for manufacturing an electronic device may also include the step of peeling off the polyimide film on which the electronic element, the like, is formed from the support.

[0103] Examples

[0104] Hereinafter, embodiments of the present invention will be described, but the scope of the present invention is not limited to the following embodiments.

[0105] Methods for Measuring Physical Properties

[0106] First, the method for measuring the physical properties of polyimide (polyimide film) will be explained.

[0107] [Light transmittance]

[0108] For each polyimide film obtained in the examples and comparative examples described below, the transmittance of light at a wavelength of 450 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer (V-650 manufactured by Nihon Bunko).

[0109] [Yellowness (YI)]

[0110] For each polyimide film obtained in the examples and comparative examples described below, the light transmittance at wavelengths from 200 nm to 800 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer (V-650 manufactured by Nihon Bunko Co., Ltd.), and the yellowness (YI) of the polyimide film was calculated from the formula described in JIS K7373-2006. If YI was 14 or less, it was evaluated as having "excellent low-colorability." On the other hand, if YI exceeded 14, it was evaluated as having "not excellent low-colorability."

[0111] [Heize]

[0112] For each polyimide film obtained in the examples and comparative examples described below, haze was measured using an integrating sphere type haze meter ("COH 300A" manufactured by Nippon Tenshoku Kogyo Co., Ltd.) according to the method described in JIS K7136-2000.

[0113] [Internal Stress]

[0114] A polyimide film was formed on a glass substrate manufactured by Corning (material: alkali-free glass, thickness: 0.7 mm, size: 100 mm × 100 mm), the amount of warping of which had been measured in advance, in the same manner as the examples and comparative examples described below, and a laminate having a polyimide film with a thickness of 10 μm on the glass substrate was obtained. In order to exclude the absorption effect of the polyimide film, the laminate was dried at 120°C for 10 minutes, and then the amount of warping of the laminate under a nitrogen atmosphere at a temperature of 25°C was measured using a thin film stress measuring device (KLA-Tencor “FLX-2320-S”). Then, from the amount of warping of the glass substrate before the formation of the polyimide film and the amount of warping of the laminate, the internal stress generated between the glass substrate and the polyimide film was calculated by Stoney's equation.

[0115] [Ritualation]

[0116] For each polyimide film obtained in the examples and comparative examples described below, the thickness direction retardation (Rth) for light with a wavelength of 550 nm was measured using a phase difference meter (Syntech’s “OPTIPRO”). Then, based on the thickness D (unit: μm) of the measurement sample (polyimide film), the value converted to a polyimide film with a thickness of 10 μm (Rth) was calculated using the following formula. 10 ) was calculated. Rth 10 It was evaluated that "retardation can be reduced" when this is 80 nm or less. Meanwhile, Rth 10 If this exceeds 80 nm, it was evaluated that "retardation is not reduced."

[0117] Rth 10 =Rth×10 / D

[0118] [Coefficient of Linear Expansion (CTE)]

[0119] Each polyimide film obtained in the examples and comparative examples described below was sampled with a width of 3 mm and a length of 10 mm and used as a sample for CTE measurement. Using a thermal analysis device (Hitachi High-Tech Science "TMA / SS7100"), the sample was heated from 10°C to 400°C at a heating rate of 10°C / min under a load of 29.4 mN, and then cooled down at a cooling rate of 40°C / min. The CTE was then calculated from the amount of deformation from 350°C to 100°C during cooling. If the CTE was 80 ppm / K or less, it was evaluated as having "excellent low thermal expansion." On the other hand, if the CTE exceeded 80 ppm / K, it was evaluated as having "not excellent low thermal expansion."

[0120] [Glass Transition Temperature (Tg)]

[0121] Each polyimide film obtained in the examples and comparative examples described below was sampled with a width of 3 mm and a length of 10 mm and used as a sample for Tg measurement. Using a thermal analysis device (Hitachi High-Tech Science "TMA / SS7100"), a load of 98.0 mN was applied to the sample, and the temperature was raised from 10°C to 450°C at a rate of 10°C / min. A TMA curve was obtained by plotting the temperature and the amount of deformation (elongation). The inflection point temperature of the obtained TMA curve (the temperature corresponding to the peak in the differential curve of the TMA curve) was set as the glass transition temperature (Tg).

[0122] [1% weight loss temperature (TD1)]

[0123] Each polyimide film obtained in the examples and comparative examples described below (specifically, a polyimide film sampled to have a weight of 10 mg) was used as a sample for measurement, and a differential thermal / thermogravimetric measurement device (Hitachi High-Tech Science "TG / DTA7200") was used to increase the temperature from 25°C to 650°C under a nitrogen atmosphere at a rate of 20°C / min, and the measurement temperature at which the weight of the sample at a measurement temperature of 150°C decreased by 1% weight relative to this reference weight was set as the 1% weight loss temperature (TD1).

[0124] Fabrication of Polyimide Membranes

[0125] The method for preparing the polyimide films of the examples and comparative examples is described below. Additionally, compounds and reagents are listed below by the abbreviations. Furthermore, for both the examples and comparative examples, the polyamide acid solution was prepared under a nitrogen atmosphere.

[0126] NMP: N-methyl-2-pyrrolidone

[0127] BPAF: 9,9-Bis(3,4-Dicarboxyphenyl)fluorene dianhydride

[0128] BPDA: 3,3',4,4'-Biphenyltetracarboxylic acid dianhydride

[0129] PMDA: Pyromylic acid dianhydride

[0130] PDA: p-phenylenediamine

[0131] PHBAAB: (2-phenyl-4-aminophenyl)-4-aminobenzoate

[0132] TFMB: 2,2'-Bis(trifluoromethyl)benzidine

[0133] DABA: 4,4'-diaminobenzanilide

[0134] BAFL: 9,9-bis(4-aminophenyl)fluoren

[0135] [Example 1]

[0136] First, a polyamide acid solution was prepared in the following procedure. 400.0 g of NMP was added as an organic solvent for polymerization to a 1 L glass separable flask equipped with a stirrer fitted with a stainless steel stirring rod and a nitrogen inlet tube. Subsequently, 19.1 g of PDA was added to the flask and dissolved while stirring the contents of the flask. Then, 80.9 g of BPAF was added to the flask while stirring the contents of the flask, and the contents of the flask were stirred for 24 hours under an atmosphere of 25°C. Then, NMP was added to the contents of the flask to obtain a polyamide acid solution such that the concentration of polyamide acid in the flask contents after stirring was 10.0 wt%.

[0137] Next, the obtained polyamide acid solution was applied onto a glass substrate (Corning Eagle XG, material: alkali-free glass, thickness: 0.7 mm, size: 150 mm × 150 mm) using a spin coater, and heated in air at 80°C for 30 minutes to obtain a laminate (polyamide acid film-containing laminate) having a film containing polyamide acid formed on the glass substrate. Subsequently, the polyamide acid film-containing laminate was heated under the following heating conditions in a nitrogen atmosphere to perform imidization of the polyamide acid, thereby obtaining a laminate having a polyimide film with a thickness of 10 μm on the glass substrate. The heating conditions for imidization were as follows: first, the atmosphere temperature was raised from 20°C to 350°C at a heating rate of 5°C / min and maintained at 350°C for 30 minutes. Then, the atmosphere temperature was raised to 420°C at a heating rate of 5°C / min and maintained at 420°C for 30 minutes. The polyimide film was peeled off from the glass substrate of the obtained laminate to obtain the polyimide film of Example 1.

[0138] [Examples 2 to 35 and Comparative Examples 1 to 7]

[0139] Polyimide films of Examples 2 to 35 and Comparative Examples 1 to 7 were each obtained by the same method as in Example 1, except that the type and ratio (input ratio) of the acid dianhydride and the type and ratio (input ratio) of the diamine were as shown in Tables 1 and 2. In addition, for any of Examples 2 to 35 and Comparative Examples 1 to 7, the total amount of acid dianhydride and the total amount of diamine were the same as in Example 1.

[0140] For Examples 1 to 35 and Comparative Examples 1 to 7, the types and proportions of acid dianhydrides and the types and proportions of diamines are shown in Tables 1 and 2. For any of Examples 1 to 35 and Comparative Examples 1 to 7, the mole fraction of each residue of polyamic acid in the prepared polyamic acid solution matched the mole fraction of each monomer (diamine and tetracarboxylic acid dianhydride) used in the synthesis of polyamic acid. In addition, in Examples 2 to 14 and 16 to 33, two types of diamines (Component 1 and Component 2) were used. In addition, in Examples 34, 35 and Comparative Examples 4 to 7, two types of acid dianhydrides (Component 1 and Component 2) were used. For any of Examples 2 to 14, Examples 16 to 35, and Comparative Examples 4 to 7, Component 1 and Component 2 were placed in a flask simultaneously. In addition, in Tables 1 and 2, the ratio values ​​of acid dianhydrides represent the content of each acid dianhydride relative to the total amount of acid dianhydrides used (unit: mol%). In addition, in Tables 1 and 2, the ratio values ​​of diamines represent the content of each diamine relative to the total amount of diamines used (unit: mol%).

[0141]

[0142]

[0143] <Measurement Results>

[0144] For each of Examples 1 to 35 and Comparative Examples 1 to 7, the measurement results of each physical property are shown in Tables 3 and 4. In addition, in Tables 3 and 4, “-” indicates that it was not measured. Also, in Tables 3 and 4, “light transmittance” is the transmittance of light with a wavelength of 450 nm.

[0145]

[0146]

[0147] The polyamic acids synthesized in Examples 1 to 35 had BPAF residues as acid dianhydride residues. The polyamic acids synthesized in Examples 1 to 35 had one or more selected from the group consisting of PDA residues and PHBAAB residues as diamine residues. In the polyamic acids synthesized in Examples 1 to 35, the content of BPAF residues was 90 mol% or more and 100 mol% or less relative to the total acid dianhydride residues.

[0148] In Examples 1 to 35, YI was 14 or less. Therefore, the polyimide films of Examples 1 to 35 exhibited excellent low color resistance. In Examples 1 to 35, Rth 10 This was 80 nm or less. Therefore, the polyimide films of Examples 1 to 35 were able to reduce retardation. In Examples 1 to 35, the CTE was 80 ppm / K or less. Therefore, the polyimide films of Examples 1 to 35 had excellent low thermal expansion.

[0149] The polyamic acids synthesized in Comparative Examples 1 to 3 did not have one or more selected from the group consisting of PDA residues and PHBAAB residues as diamine residues. The polyamic acids synthesized in Comparative Examples 2 and 3 did not have BPAF residues as acid dianhydride residues. In the polyamic acids synthesized in Comparative Examples 4 to 7, the content of BPAF residues was less than 90 mol% relative to the total acid dianhydride residues.

[0150] In Comparative Example 1, the CTE exceeded 80 ppm / K. Therefore, the polyimide film of Comparative Example 1 did not exhibit excellent low thermal expansion properties. In Comparative Example 2, Rth 10 This exceeded 80 nm. Therefore, the polyimide film of Comparative Example 2 did not have reduced retardation. In Comparative Examples 2 to 7, YI exceeded 14. Therefore, the polyimide films of Comparative Examples 2 to 7 did not have excellent low color resistance.

[0151] From the above results, it was shown that the polyimide obtained from the polyamide acid related to the present invention can reduce Rth and also exhibits excellent low colorability and low thermal expansion.

Claims

Claim 1 A polyamide acid having a tetravalent organic group represented by the following general formula (1) as a tetracarboxylic acid dianhydride residue, and having a p-phenylenediamine residue and a 4,4'-diaminobenzanilide residue as a diamine residue, wherein the content of the tetravalent organic group represented by the following general formula (1) is 90 mol% or more and 100 mol% or less relative to the total tetracarboxylic acid dianhydride residue, and the content of the 4,4'-diaminobenzanilide residue is 1.0 mol% or more relative to the total diamine residue. (Among the above general formula (1), R 1 and R 2 Each represents, independently, a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 14 carbon atoms, a hydroxyl group, a nitrile group, a nitro group, a carboxyl group, or an amide group. Claim 2 In claim 1, among the above general formula (1), R 1 and R 2 is a polyamide acid, all representing hydrogen atoms. Claim 3 The polyamide acid according to claim 1, further having one or more selected from the group consisting of 2,2'-bis(trifluoromethyl)benzidine residues and 9,9-bis(4-aminophenyl)fluorene residues as diamine residues. Claim 4 A polyamide acid solution containing a polyamide acid and an organic solvent as described in any one of claims 1 to 3. Claim 5 Polyimide that is an imid of a polyamide acid as described in any one of paragraphs 1 to 3. Claim 6 In paragraph 5, a polyimide having a glass transition temperature of 350°C or higher. Claim 7 Polyimide film comprising the polyimide described in paragraph 5. Claim 8 A laminate having a support and a polyimide film as described in claim 7. Claim 9 An electronic device having a polyimide film described in claim 7 and an electronic element disposed on said polyimide film. Claim 10 A method for manufacturing a polyimide film, wherein a polyamide acid solution described in claim 4 is applied onto a support to form a coating film containing said polyamide acid, and said coating film is heated to imidize said polyamide acid. Claim 11 A method for manufacturing a polyimide film according to claim 10, wherein the maximum temperature when heating the coating film is 380°C or higher and 500°C or lower. Claim 12 A method for manufacturing a polyimide film according to claim 11, wherein the heating time at the maximum temperature is 5 minutes or more and 60 minutes or less. Claim 13 A method for manufacturing a polyimide film according to claim 10, wherein the polyimide film obtained by heating the coating film is peeled off from the support. Claim 14 A method for manufacturing a polyimide film according to claim 13, wherein the polyimide film is peeled off from the support by laser irradiation.

Citation Information

Patent Citations

  • Optical film and image display device

    JP2005306983A

  • Polyimide precursor, resin composition containing the same, and cured product

    JP2020164597A